Exploring the motivations and social organisation of intoxication in prison settings - Kolind, Torsten (Routledge handbook of intoxicants and intoxication, 2023)
Studies on drug and alcohol use in prison settings have primarily focused on prevalence, harms, treatment and policies, whereas the topic of ‘intoxication’ in prison settings has rarely been explored. In this chapter, we aim to synthesise existing social science literature on the use of drugs in prisons with theoretical perspectives from penology and drug studies in order to investigate prisoners’ motivations for drug use and intoxication in prisons, the role that drugs play as part of the social organisation of people in prisons, and the possible relationship between intoxication and pleasure in the prison context. The chapter also offers an overview of prevalence rates of drug use before, during and after prison to contextualise the analysis. We hope that the chapter can inspire future research on the many meanings drugs and intoxication take in prison settings and the many diverse practices of both prisoners and staff related to drug and alcohol issues.